Numerical modeling and dynamic behavior of a railway concrete bridge over the Vindel River in Sweden - He, Guojing; Bennitz, Anders; Enochsson, Ola; Elfgren, Lennart; Paulsson, B.; Töyrä, B.; Olofsson, P.; Kronborg, A. (Luleå tekniska universitet, 2006)
The Vindel Railway Bridge in northern Sweden is composed of a concrete deck, columns and an arch with a span of 110 m and a height of 22 m. In order to check the possibility to increase the axle load from 225 kN to 250 kN, the properties of the bridge needed to be evaluated. Especially, the dynamic behavior of the bridge is an important factor as it is affecting the load bearing capacity and the serviceability. In this paper, two types of three-dimensional (3-D) finite element models have been developed. One uses shell elements and the other uses beam elements. Based on the 3-D FE models, the effects of nonstructural mass, side spans and connection between columns and deck on the dynamic behavior are discussed. Furthermore, field test data from passing through train are compared with the results calculated by the models. The numerical simulations of the dynamic response coincide reasonably well with the field test data. Godkänd; 2006; 20061111 (ysko)